Special Spot Day Care Graduation in Watkins' Backyard - Watkins, Howard::::::::: (1983)
Teacher Eva Garza holding Devon Bleile-Kratzer, Art Wille, Seth Tilley, Adam Watkins, Kent Tracy holding Jimmy Jones and ?